Investigating learning transfer on an adjunct writing course for L2 English speaking trainee teachers. (1st March 2022) - Gordon, Matthew
Abstract : This study represents an account and analysis of an adjunct writing course designed to assist L2 English speaking teachers with the written assignments on a Trinity College London CertTESOL course. It aims to discover the usefulness of such a course by uncovering participants' perspectives regarding learning transfer from the writing course to the assignments. Specifically, it attempts to discover the extent to which learners perceived their ability to use content taught on the writing course in their assignments and the factors that assisted and hindered them in doing so. It is hoped that the study will lead to understandings about learning transfer which can be applied more widely in English for Academic Purposes (EAP) teaching. Semi-structured interviews were conducted with teachers who took the writing course and the transcripts were analyzed inductively. Major findings include the occurrence of near and far transfer, the encouragement of this transfer by the ability of participants to process general concepts and apply them in tasks which were similar to those in the assignments on the CertTESOL and the usefulness of syllabus design based on knowledge of the linguistic demands of those assignments, the common issues faced by learners when completing them, and the expectations of CertTESOL tutors.